For the Life of the World: Toward an Appraisal of Its Use of Scripture - Clifton Black, C. (Theology today, 2022)
Adopting David Kelsey's study of modern theologians’ uses of Scripture (1975), this article investigates the theoretical basis and practical outcomes for the procedure exemplified in For the Life of the World: Toward a Social Ethos of the Orthodox Church (2020). A consonance of its interpretive postulates and manner of scriptural appeals is demonstrable, coupled with diminished attention to biblical breadth and cogent scriptural warrants.